The readiness of retailers in Malaysia to accept mobile payments as a payment alternative / Nur Syazana Mohd Nasir and Azlyantiny Mohammad - Mohd Nasir, Nur Syazana; Mohammad, Azlyantiny (Universiti Teknologi MARA, Kedah, 2024)
This review paper examines the current state of readiness among retailers in Malaysia to accept mobile payments as a means of payment. The study draws upon academic literature from various disciplines, including marketing, finance, and information systems, to gain comprehensive insights into the factors influencing retailers' adoption of mobile payment technologies. Through the analysis of relevant research articles, this paper identifies the drivers and barriers associated with mobile payment adoption in the Malaysian retail context and discusses the implications for retailers seeking to capitalize on the growing trend of digital payments in the country.